2023
DOI: 10.1007/s12665-023-10879-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of loess planar erosion and numerical simulation based on CFD–DEM coupling model

Abstract: Planar erosion is an important mode of soil erosion, which occurs in the process of loess slope erosion, gully erosion, and cave erosion. It is of great significance to understand the characteristics and mechanism of planar erosion to reveal the mechanism of loess erosion and the prevention and treatment of soil and water loss. In this paper, a series of loess planar erosion tests have been carried out through self-developed large-scale loess scour instrument. The erosion process and stage characteristics of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Pan et al [15] investigated the effect of head rise rates on erosion using an indoor device and found that different head rise rates led to different internal erosion damage patterns. Wen et al [16] used a self-developed large loess-scouring instrument to analyze and summarize the erosion process and stage characteristics of subsurface erosion under different conditions and revealed the intrinsic mechanisms of the plane erosion process of loess in the stages of different erosion characteristics. The behaviors of soils are highly stochastic under seepage.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al [15] investigated the effect of head rise rates on erosion using an indoor device and found that different head rise rates led to different internal erosion damage patterns. Wen et al [16] used a self-developed large loess-scouring instrument to analyze and summarize the erosion process and stage characteristics of subsurface erosion under different conditions and revealed the intrinsic mechanisms of the plane erosion process of loess in the stages of different erosion characteristics. The behaviors of soils are highly stochastic under seepage.…”
Section: Introductionmentioning
confidence: 99%